Sistem Informasi Pemesanan Lapangan Pada Arena Futsal Kelapa Dua Berbasis Web - Eko Setia Budi; Raden Bagus Dimas Putra; Abdul Rahman Kadafi (Universitas Budi Darma, 2021)
Kelapa Dua Futsal Arena is an individual company engaged in the futsal field reservation service. In this futsal ordering service, the service factor affects the smooth operation of the information. With good information system services and also optimizing profits on the futsal field ordering service. Therefore a website is needed in order to simplify the process of ordering the futsal field and provide information on the availability of empty fields to the orderer through the ordering information system.